Labour-Saving Automation and Occupational Exposure: A Text-Similarity Measure - Fabio Montobbio; Jacopo Staccioli; Maria Enrica Virgillito; Marco Vivarelli (Institute of Labor Economics (IZA), 2021)
This paper represents one of the first attempts at building a direct measure of occupational exposure to robotic labour-saving technologies. After identifying robotic and LS robotic patents retrieved by Montobbio et al. (2022), the underlying 4-digit CPC definitions are employed in order to detect functions and operations performed by technological artefacts which are more directed to substitute the labour input. This measure allows to obtain fine-grained information on tasks and occupations according to their similarity ranking. Occupational exposure by wage and employment dynamics in the United States is then studied, complemented by investigating industry and geographical penetration rates.
Keywords: O33; J24; 330; labour-saving technology; natural language processes; labour markets; technological unemployment